Functional characterization and differential expression studies of squalene synthase from Withania somnifera - Gupta, Neha; Sharma, Poonam; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2012)
Squalene synthase (SQS: EC 2.5.1.21) is a potential branch point regulatory enzyme and represents the first committed step to diverge the carbon flux from the main isoprenoid pathway towards sterol biosynthesis. In the present study, cloning and characterization of Withania somnifera squalene synthase (WsSQS) cDNA was investigated subsequently followed by its heterologous expression and preliminary enzyme activity. Two different types of WsSQS cDNA clones (WsSQS1and WsSQS2) were identified that contained an open reading frames of 1,236 and 1,242 bp encoding polypeptides of 412 and 414 amino acids respectively. Both WsSQS isoforms share 99 % similarity and identity with each other. WsSQS deduced amino acids sequences, when compared with SQS of other plant species, showed maximum similarity and identity with Capsicum annuum followed by Solanum tuberosum and Nicotiana tabacum. To obtain soluble recombinant enzymes, 24 hydrophobic amino acids were deleted from the carboxy terminus and expressed as 6X His-Tag fusion protein in Escherichia coli. Approximately 43 kDa recombinant protein was purified using Ni-NTA affinity chromatography and checked on SDS-PAGE. Preliminary activity of the purified enzymes was determined and the products were analyzed by gas chromatograph-mass spectrometer (GC-MS). Quantitative real-time PCR (qRT-PCR) analysis showed that WsSQS expresses more in young leaves than mature leaves, stem and root.
Keywords: Gas chromatograph-Mass Spectrometer (GC-MS); qRT-PCR; Squalene synthase; Withania somnifera

Functional characterization of a flavonoid glycosyltransferase gene from withania somnifera (Ashwagandha) - Singh, Somesh; Vishwakarma, Rishi. K.; Kumar, R. J. Santosh; Sonawane, Prashant D.; Ruby; Khan, Bashir Mohammad (Applied Biochemistry and Biotechnology, 2013)
Glycosylation of flavonoids is mediated by family 1 uridine diphosphate (UDP)-dependent glycosyltransferases (UGTs). Until date, there are few reports on functionally characterized flavonoid glycosyltransferases from Withania somnifera. In this study, we cloned the glycosyltransferase gene from W. somnifera (UGT73A16) showing 85-92 % homology with UGTs from other plants. UGT73A16 was expressed as a His(6)-tagged fusion protein in Escherichia coli. Several compounds, including flavonoids, were screened as potential substrates for UGT73A16. HPLC analysis and hypsochromic shift indicated that UGT73A16 transfers a glucose molecule to several different flavonoids. Based on kinetic parameters, UGT73A16 shows more catalytic efficiency towards naringenin. Here, we explored UGT73A16 of W. somnifera as whole cell catalyst in E. coli. We used flavonoids (genistein, apigenin, kaempferol, naringenin, biochanin A, and daidzein) as substrates for this study. More than 95 % of the glucoside products were released into the medium, facilitating their isolation. Glycosylation of substrates occurred on the 7- and 3-hydroxyl group of the aglycone. UGT73A16 also displayed regiospecific glucosyl transfer activity towards 3-hydroxy flavone compound, which is the backbone of all flavonols and also for a chemically synthesized compound, not found naturally. The present study generates essential knowledge and molecular as well as biochemical tools that allow the verification of UGT73A16 in glycosylation.
Keywords: Flavonoid; glycosylation; Glycosyltransferase; Hypsochromic shift; Plant secondary product glycosyltransferase (PSPG); Withania somnifera

Functional characterization of a glucosyltransferase specific to flavonoid 7-O-glucosides from withania somnifera - Kumar, R. J. Santosh; Ruby; Singh, Somesh; Sonawane, Prashant D.; Vishwakarma, R. K.; Khan, Bashir Mohammad (Plant Molecular Biology Reporter, 2013)
Flavonoids are a large class of phenylpropanoid-derived secondary metabolites, which are usually glycosylated by UDP-glycosyltransferases with one or more sugar groups. Here, we report the cloning and biochemical characterization of a flavonoid glycosyltransferase gene from Withania somnifera (WsGT), which is an important medicinal plant used in Ayurvedic formulations. Using PCR primers, designed for a highly conserved region of previously reported glycosyltransferases, we were able to isolate the corresponding fragment of the WsGT gene. Rapid amplification of cDNA ends (RACE) was then employed to isolate full-length cDNA, which had an open reading frame of 1,371 bp that encode for 456 amino acids. Phylogenetic analysis indicated that WsGT was similar to that of family 1 GT-B glycosyltransferase. Biochemical analysis revealed that WsGT interacts with UDP-glucose and was capable of regiospecifically glycosylating flavonoid-7-ols, such as apigenin, naringenin, luteolin, diadzein and genistein. Expression profiling studies showed that WsGT was highly expressed in young and mature leaves of W. somnifera. Furthermore, exposure to salicylic acid enhanced the expression of WsGT in the leaves and heat shock treatment resulted in decreased expression of WsGT after an initial increase. This may suggest the role of WsGT in response to abiotic/biotic stresses.
Keywords: Diadzein; Flavonoids; Glycosyltransferase; Withania somnifera